Design of Arduino Based Door Bell for Physically Challenged People (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a day, doorbells are often seen in every house. Also it is one of the most common devices used in house to alert the person inside home is doorbell. It is used to open the door if someone has arrived. In this work is developing a special type of doorbell for physically challenged a person who has hearing loss. An ultrasonic and PIR sensor is used to detect the person standing in the door. Through Arduino interface LCD, ZigBee transceiver signal will be transmitted and received. Once ZigBee is receiving the signal, vibration motor will be vibrated. So, the vibration signal will get alert, which a person is standing in the door.